Cotton Cultural Practices and Fertility Management - David Wright; Jim Marois; Jim Rich (EDIS)
This document is SS-AGR-194, a publication of the Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: September 2003.